Impact of Covid-19 on banking performance of Mercantile Bank Ltd. compared to some selective commercial banks of Bangladesh - Tahsin, Hredita (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.